Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijerph17113760
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Exercise Program Reduces Frailty and Inflammatory Biomarkers and Improves Physical Performance in Community-Dwelling Older Adults: A Randomized Controlled Trial

Abstract: The efficacy of exercise to reverse frailty in the aging population has not been extensively investigated. This study aimed to investigate the effectiveness of a multicomponent exercise program (MCEP) on frailty, physical performance (handgrip strength, Berg Balance Scale (BBS), Timed Up and Go test (TUG), and VO2Max), blood biomarkers (Interleukin-6 (IL-6) and C-reactive protein (CRP)) in frail older adults. A randomized controlled trial using an allocation concealment method, included 64 older adults (77.78 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
173
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(213 citation statements)
references
References 53 publications
(72 reference statements)
11
173
1
2
Order By: Relevance
“…This study finding is in the same line with that of the study conducted by Sadjapong et al, 2020 [34], who revealed that the multicomponent exercise program delays frailty in community dwelling elders. Furthermore, this study result is congruent with that of the study performed by Yu et al, 2020 [35], who revealed that the physical exercise is more beneficial to frail and pre-frail elders when compared with other types of interventions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study finding is in the same line with that of the study conducted by Sadjapong et al, 2020 [34], who revealed that the multicomponent exercise program delays frailty in community dwelling elders. Furthermore, this study result is congruent with that of the study performed by Yu et al, 2020 [35], who revealed that the physical exercise is more beneficial to frail and pre-frail elders when compared with other types of interventions.…”
Section: Discussionsupporting
confidence: 93%
“…This tool was established by the researcher grounded on pertinent literature to assess the older adults' own beliefs in his/her capabilities to successfully execute exercises. The total score was categorized as follow; a score of (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) indicating low selfefficacy, whereas the score of (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) indicating the moderate self-efficacy, and the score of (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) indicating high self-efficacy. The tool was tested for its validity and reliability and the results indicated that it is valid and reliable (r=0.762).…”
Section: Tool (Vi): Exercise Self-efficacy Scalementioning
confidence: 99%
“…General physical exercise guidelines often focus on prevention of pathologies. Population level preventive efforts ideally before the onset of functional decline have been tried out and tested in many countries (12)(13)(14)(15)(16). Unfortunately, a limited amount of physical exercise strategies are planned to minimize exercise-related impact on function and/or ability to perform ADLs or in other domains of intrinsic capacity on older population, probably related to the scarcity of research in the area (4).…”
mentioning
confidence: 99%
“…Low levels of physical exercise together with an unhealthy diet are major risk factors for sarcopenia, which together with other biological factors (e.g., hormones, inflammation and insulin resistance) and psychosocial factors (e.g., depression, social isolation, and loneliness) contribute to the decline in skeletal muscle performance with advancing age [155]. A wealth of evidence highlights the positive benefits of physical exercise in enhancing muscle function and/or preventing mobility and physical limitations [156][157][158]. The Lifestyle Interventions and Independence for Elders (LIFE) study showed that walking and low-intensity resistance training reduced the risk of major mobility disability in mobility-limited older adults over the course of two years in a dose-dependent manner when compared with a health education program with the greatest benefit by adding at least 48 min of physical activity to their weekly routine [159].…”
Section: Exercise and Muscle Strengtheningmentioning
confidence: 99%